Influence of Grafting On the Growth, Yield, Quality and Shelf Life of Tomatoes (Solanum Lycopersicum L.) Grafted Onto Three Solanum Species - Ofori, E. (University of Ghana, 2015)
A pot experiment was carried out from 15th December, 2014 to 20th June, 2015 at the University of Ghana Forest and Horticultural Crop Research Centre (FOHCREC), Okumaning under greenhouse conditions in a randomized complete block design to investigate the influence of grafting on growth, yield, quality and shelf life of tomato grafted onto three solanum species. Two tomato varieties ‘Fadeεbege’, and ‘Nkansah HT’ were used as scions and three solanum specie ‘Gboma’, ‘Black Beauty’ and ‘Obaapa’ were used as rootstocks. The rootstock-scion combinations were, ‘Fadeεbege/Gboma’, ‘Nkansah HT/ Gboma’, ‘Fadeεbege / Black Beauty’, ‘Nkansah HT/ Black Beauty’, ‘Fadeεbege / Obaapa’, ‘Nkansah HT / Obaapa’, non-grafted ‘Fadeεbege’ and non- grafted ‘Nkansah HT’. The results indicated that, grafting tomatoes onto Black Beauty performed better in terms of plant growth, yield quality, and shelf life than non-grafted plants. Earliness characterized by days to flowering and harvesting was significantly different for tomatoes grafted onto Black Beauty (21 days and 51 days) compared to non-grafted ‘Fadeεbege’ (31 days and 60 days) and non-grafted ‘Nkansah HT’ (34 days and 67 days). Fruit number and total yield of tomato grafted onto Black Beauty (27 and 5.18 t/ha) were higher compared to non-grafted ‘Fadeεbege’ (18 and 3.30 t/ha) and ‘non-grafted Nkansah HT’ (23 and 3.94 t/ha) respectively. However, the shelf life of tomatoes grafted onto ‘Gboma’ (46 days) and Black Beauty (43 days) were significantly higher compared to non-grafted ‘Fadeεbege’ (24 days) and non-grafted ‘Nkansah HT’ (41 days). Grafting significantly affected the brix, TA, TSS:TA, pH, vitamin C and lycopene content of grafted plants compared to non-grafted plants. The study demonstrated that grafting tomato onto ‘Black Beauty’ rootstock enhanced growth, yield, fruit quality and extended shelf life. The rootstock ‘Black Beauty’ may be recommended for use as a suitable rootstock for tomato grafting.
Thesis (MPhil.) - University of Ghana, 2015